2018
DOI: 10.2464/jilm.68.660
|View full text |Cite
|
Sign up to set email alerts
|

Tearing mechanism for high-strength Al–Zn–Mg–Cu alloys in hot extrusion

Abstract: In hot extrusion, tearing plays an important role on surface quality of profiles. In this study, extrudability of 7075 aluminum alloy without tearing was quantified by extrusion limit diagram, which is a relationship between temperatures and speeds. Tearing appearance and distribution of elements were investigated to assess tearing mechanism. According to the diagram, tearing easily occurrs at high temperature and high speed conditions. Micro-solid bridge was observed at tearing surface to indicate the localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Figure 13 shows the tearing size-stroke diagram for various die coatings. In the previous study [8], it was shown that tearing increased with the stroke, which is consistent with the obtained result. Furthermore, the tearing depth increases with the stroke for all extrusion conditions, but the tearing depth of the AlCrN die is smaller than those of the nitriding, TiAlN, and DLC dies.…”
Section: Effect Of Die Coating On Tearing Of A7075 During Hot Extrusionsupporting
confidence: 92%
See 1 more Smart Citation
“…Figure 13 shows the tearing size-stroke diagram for various die coatings. In the previous study [8], it was shown that tearing increased with the stroke, which is consistent with the obtained result. Furthermore, the tearing depth increases with the stroke for all extrusion conditions, but the tearing depth of the AlCrN die is smaller than those of the nitriding, TiAlN, and DLC dies.…”
Section: Effect Of Die Coating On Tearing Of A7075 During Hot Extrusionsupporting
confidence: 92%
“…Our previous studies showed that tearing is more likely to occur under high-temperature and highvelocity conditions [8]. We have reported that tearing is caused by the segregation and localized melting of soluble intermetallic compounds containing Zn and Mg in the crystalline structure.…”
Section: Introductionmentioning
confidence: 96%
“…The tearing depth of extrudate with and without cooling was about 1.50-300 µm, and 100-200 µm, respectively. The tearing occurs in the coarsened recrystallized microstructure layer at the edge of extrudate due to the heat generated during processing, which leads to crack propagation [4][5]. The cooling of the extrudate also inhibited the coarsening of the crystalline microstructure at the extrudate edge, which is thought to have reduced the tearing depth.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, AA7075 is one of the least deformable aluminum alloys and has high flow stress, which significantly limits the extrusion speed from 0.8 to 2.0 m/min. In our previous research, we reported that tearing was caused by low-melting intermetallic compounds containing magnesium (Mg) and zinc (Zn) [3]. It reported that the intermetallic compound with a low melting point locally melted due to the heat generated by the forming process.…”
Section: Introductionmentioning
confidence: 99%